Neonatal screening and a new cause of congenital central hypothyroidism - Toshihiro Tajima; Akie Nakamura; Shuntaro Morikawa; Katsura Ishizu (Korean Society of Pediatric Endocrinology, 2014)
Congenital central hypothyroidism (C-CH) is a rare disease in which thyroid hormone deficiency is caused by insufficient thyrotropin (TSH) stimulation of a normally-located thyroid gland. Most patients with C-CH have low free thyroxine levels and inappropriately low or normal TSH levels, although a few have slightly elevated TSH levels. Autosomal recessive TSH deficiency and thyrotropin-releasing hormone receptor-inactivating mutations are known to be genetic causes of C-CH presenting in the absence of other syndromes. Recently, deficiency of the immunoglobulin superfamily member 1 (IGSF1) has also been demonstrated to cause C-CH. IGSF1 is a plasma membrane glycoprotein highly expressed in the pituitary. Its physiological role in humans remains unknown. IGSF1 deficiency causes TSH deficiency, leading to hypothyroidism. In addition, approximately 60% of patients also suffer a prolactin deficiency. Moreover, macroorchidism and delayed puberty are characteristic features. Thus, although the precise pathophysiology of IGSF1 deficiency is not established, IGSF1 is considered to be a new factor controlling growth and puberty in children.